Local BMP-2 application can rescue the delayed osteotomy healing in a rat model - Wildemann, Britt; Lange, K.; Strobel, C.; Fassbender, M.; Willie, B.; Schmidmaier, Gerhard (Injury, 2011)
Delayed healing is still a severe complication in the clinic. The aim of the present study was to investigate the effect of locally delivered BMP-2 incorporated in a poly(d,l-lactide) (PDLLA) implant coating in a rat model with delayed tibial healing. The healing delay in this model is not caused by mechanical instability or additional tissue manipulation and presents therefore a common and challenging clinical situation of impaired healing. Radiological, histological and biomechanical evaluations were performed at days 5, 10, 28, 42, and 84 after tibial osteotomy. The control group showed a delayed healing without complete bridging and without reaching the biomechanical stability of the contralateral tibiae after 84 days. The mechanical stability of the BMP-treated tibiae showed a significant increase at days 28 and 42 compared to the control group and exceeded the stability of the intact contralateral tibiae. Less cartilage was detected at day 28 and the mineralisation was significantly enhanced at day 42 due to the local BMP application. Looking at the early healing phase (day 10) a reduced vascularisation was seen in the BMP group. This reflects the situation seen during normal healing, whereas the delayed healing in the present model had an increased vascularisation. The present study clearly demonstrates that local BMP-2 application can stimulate delayed healing in a clinically relevant animal model.
Available online 4 December 2010
Gesehen am 03.11.2022